This I Believe - Stewart, George (Tufts Archival Research Center, 2006)
Lt. Col. George Stewart, Air Force Interpreter of American Life and Culture to the British Armed Forces, describes how he developed a moral code based on friendliness, and explains how his faith in people developed because of his neighbors' friendliness, and how Jesus demonstrated God's friendliness during His time on earth.